Spesifikasi dan Interpretasi Air Drainase di CPP Gundih - Putri, Sekar Mahardika; Z, Ainul Qodri; Persada, Asa Aditya (Action Research Literate, 2025)
This study examines the quality of drainage water at the Central Processing Plant (CPP) Gundih, a natural gas processing facility owned by PT. Pertamina EP Asset 4 Cepu Field. Wastewater generated from gas processing activities and office operations is discharged through northern and southern sewer systems before being released into the environment. The research was conducted over 3 months with weekly sampling to test 5 water quality parameters including pH, temperature, Total Suspended Solids (TSS), Total Dissolved Solids (TDS), and Chemical Oxygen Demand (COD). Results show that temperature parameters met wastewater quality standards (BMAL) with a maximum value of 31.5°C, still below the 40°C standard. pH parameters fluctuated with several values outside the 6-9 standard range, especially in the northern sewer reaching 2.5 and 9.39. TSS and TDS mostly met oil industry waste standards, but some measurements exceeded domestic waste quality standards. COD showed high values exceeding standards, with the highest values reaching 2170 mg/L in the southern sewer and 1080 mg/L in the northern sewer. This study recommends implementing additional treatment systems for COD parameters and strict monitoring of pH fluctuations to ensure wastewater quality complies with environmental regulations.